1992
DOI: 10.2527/1992.7041091x
|View full text |Cite
|
Sign up to set email alerts
|

Bioeconomic evaluation of embryo transfer in beef production systems: III. Embryo lines for producing bulls

Abstract: A model was developed for the economic evaluation of embryos for producing bull lines for use in commercial beef production. The fundamental concept underlying the model is that a cloned and sexed embryo of known genetic characteristics for beef traits is used to produce a bull. After reaching physiological maturity, the bull is used in natural matings. Equations relating feed energy requirements and growth rates based on NRC requirements and costs and returns discounted to present value allow investigation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
1
4

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 7 publications
0
3
1
4
Order By: Relevance
“…Ruvuna et al (1992) found major increases in the proportion of males when using sexed sperm to produce bulls. Smeaton & Vivanco (2002) noted that the value of sexed semen in ET beef cattle was dependent on the cost paid for males and females at birth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ruvuna et al (1992) found major increases in the proportion of males when using sexed sperm to produce bulls. Smeaton & Vivanco (2002) noted that the value of sexed semen in ET beef cattle was dependent on the cost paid for males and females at birth.…”
Section: Discussionmentioning
confidence: 99%
“…Aspects of the viability of sexed semen were also studied by Ruvuna et al (1992) and Madalena et al (2004). In these studies, the NPV was used to evaluate the use of sexed semen in AI and ET, which showed promising expectations for the implementation of this biotechnology.…”
Section: Discussionmentioning
confidence: 99%
“…A sexagem de espermatozoides tem valor econômico significativo nos animais de interesse zootécnico com aptidão para produção de leite ou carne e em sistemas em que a produtividade é favorecida pela progênie de um dos sexos (Taylor et al, 1985;Van Vleck et al, 1987;Ruvuna et al, 1992;Hohenboken, 1999).…”
Section: Introductionunclassified
“…Na produção de animais para abate, o peso da carcaça num macho, aos 24 meses é cerca de 25 % maior que o peso da carcaça numa fêmea da mesma idade. O valor de um rebanho com 100 % de machos vai ser 34 % maior, comparado com um rebanho composto de 40 % de machos (RUVUNA et al, 1992). Nos programas de cruzamento industrial a pré-seleção do sexo maximiza a produtividade devido às diferenças entre os sexos nas características de carcaça.…”
Section: I T E R a T U R A | 26unclassified
“…Vários autores registraram o valor econômico significativo da pré-seleção de sexo na pecuária de leite e de corte, atividades onde a produtividade é favorecida quando a progênie é constituída, em sua maioria, por um dos sexos (NICHOLAS; SMITH, 1983;TAYLOR et al, 1985;VAN VLECK et al, 1987;RUVUNA et al, 1992). A pré-seleção do sexo pode acelerar o progresso genético como também, beneficiar o manejo e a eficiência produtiva PARRILLA et al, 2005).…”
Section: Introductionunclassified